2006
DOI: 10.1007/s10840-006-9003-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early recurrence and delayed cure after segmental pulmonary vein isolation for paroxysmal atrial fibrillation without structural heart disease

Abstract: Elderly patients with left atrial enlargement and a high dispersion of P wave are susceptible to ERAF after a single PVI. Left atrial enlargement is the only independent predictor of ERAF. Among patients with ERAF, those with less P-wave dispersion and less left atrial diameter have a higher probability of delayed cure. P-wave dispersion can independently predict delayed cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
68
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 28 publications
10
68
0
1
Order By: Relevance
“…Herein, we report a 52% incidence of ERAF <3 months of an index cryoballoon ablation procedure, which is consistent with nonrandomized observational studies after radiofrequency catheter ablation (16%-65%) as well as previous studies of cryoballoon ablation (44%). [3][4][5][6][7][8][9] Reassuringly, although ERAF was a relatively common occurrence after cryoballoon ablation, approximately half of these patients did not continue to have AF at longer-term follow-up, suggesting that transient periprocedural arrhythmogenicity is the predominant mechanism of ERAF in a subset of patients undergoing cryoballoon and RF ablation (44% with ERAF remained AF-free at 1 year, similar to the 46% rate reported after radiofrequency catheter ablation). [3][4][5][6][7][8] Nevertheless, a significant proportion of patients undergoing repeat cryoballoon ablation had early reconnection (52% of PVs).…”
Section: Incidence Of Early and Late Recurrencesupporting
confidence: 57%
See 1 more Smart Citation
“…Herein, we report a 52% incidence of ERAF <3 months of an index cryoballoon ablation procedure, which is consistent with nonrandomized observational studies after radiofrequency catheter ablation (16%-65%) as well as previous studies of cryoballoon ablation (44%). [3][4][5][6][7][8][9] Reassuringly, although ERAF was a relatively common occurrence after cryoballoon ablation, approximately half of these patients did not continue to have AF at longer-term follow-up, suggesting that transient periprocedural arrhythmogenicity is the predominant mechanism of ERAF in a subset of patients undergoing cryoballoon and RF ablation (44% with ERAF remained AF-free at 1 year, similar to the 46% rate reported after radiofrequency catheter ablation). [3][4][5][6][7][8] Nevertheless, a significant proportion of patients undergoing repeat cryoballoon ablation had early reconnection (52% of PVs).…”
Section: Incidence Of Early and Late Recurrencesupporting
confidence: 57%
“…[3][4][5][6] Although relatively common, the long-term clinical significance of these early recurrences remains controversial because a significant number of patients remain free of late recurrent arrhythmias despite ERAF. [3][4][5][6][7][8] Although studies have retrospectively examined clinical variables associated with early and late arrhythmic recurrence after radiofrequency ablation, there is limited evidence regarding the prognostic significance of ERAF after cryoballoon ablation. 6,9 Moreover, the effect of early reablation (ie, within the 3-month blanking period) in patients with early recurrences after cryoballoon ablation remains unknown.…”
mentioning
confidence: 99%
“…In previous RF ablation studies early recurrence was observed in 33.8-54% of patients [32][33][34][35], so early recurrence was traditionally seen as a benign process not affecting long term results. Then, a lot of studies showed that ERAF was an important risk factor for late recurrence of AF [33,[35][36][37][38][39][40].…”
Section: Early Recurrence Of Af (Eraf)mentioning
confidence: 98%
“…253,329,436,684,932,935,970,971,972 Because these arrhythmias do not definitively indicate therapy failure over the long term (only half of these patients will manifest later recurrences), this period is also referred to as the blanking or therapy stabilization period. 935,973 It is also important to recognize that the later AF recurrences are observed during the blanking phase, the lower the chance of long-term success.…”
Section: Early Recurrence After Ablationmentioning
confidence: 99%
“…On the other hand, up to 60% of the patients experiencing this event within the first months postablation will not have any further arrhythmias during long-term follow-up. 253,436,970,971,994 Therefore, reablation is not recommended in an ERAF that might be a transient phenomenon. 2 …”
Section: Early Reablationmentioning
confidence: 99%